(untitled) (Physical Education, Health and Social Sciences, 2026)
Human papillomavirus (HPV) infection is a major cause of cervical and other anogenital cancers. Despite the effectiveness and safety of HPV vaccination, its uptake remains suboptimal in several regions. Healthcare professionals (HCPs), particularly doctors and nurses, are key influencers of vaccine acceptance. This study assessed doctors’ and nurses’ knowledge and attitudes toward the HPV vaccine and identified barriers influencing their recommendation behaviors. A cross-sectional descriptive study was conducted among 200 healthcare professionals (100 doctors and 100 nurses) from a tertiary hospital. Data were collected using a validated, self-administered questionnaire covering demographics, knowledge, attitudes, and barriers to vaccine advocacy. Descriptive and inferential statistics, including t-tests, chi-square tests, and Pearson’s correlation, were performed at a significance level of p ≤ 0.05. Doctors demonstrated significantly higher mean knowledge scores (15.2 ± 3.8) than nurses (12.5 ± 4.2; p = 0.03). Most respondents expressed positive attitudes toward HPV vaccination, with 82.5% agreeing or strongly agreeing to recommend it to their patients. Common barriers included a lack of patient demand (47.5%), limited consultation time (37.5%), and cultural or religious concerns (27.5%). A significant positive correlation was found between knowledge and attitude toward recommending the vaccine (r = 0.42, p < 0.01). Conclusion: Knowledge positively influenced healthcare professionals’ attitudes toward HPV vaccination. Addressing knowledge gaps through targeted education and institutional support can enhance healthcare providers’ advocacy and potentially improve HPV vaccine uptake in clinical practices.